Peran Gender dalam Novel "Big Little Lies" - Angelina, Veren; Arianto, Tomi (BASIS (Bahasa dan Sastra Inggris), 2022)
This research describes family gender roles in Big Little Lies novel. Gender roles discussion has been important to see how social creates expectation or standard that men and women should behave. Society gives appropriate role to appropriate gender. In order to describe this phenomenon in the novel, the researcher used Eagly’s social role theory with feminist approach. The research is designed with qualitative approach. In collecting and analyzing the data, the research applied method of documentation and content analysis. The result showed that there are two kinds of gender roles in family domain in the novel; the breadwinner and the homemaker. Mainly, women were expected to be the homemaker whereas men were expected to be the breadwinner. The expectation came from the typical activity of men and women in the novel’s environment. However, the research also found that agentic women like Madeline, Renata, and Jackie, they could participate in the role of the breadwinner. Communal men like Ed, Jonathan, and Stu, they could participate in the role of homemaker. The research concluded that the novel’s society did not project the typical gender roles strictly because husbands and wives in the novel are allowed to shift roles.